2019
DOI: 10.3758/s13423-018-01566-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting attention shifting abilities from self-reported media multitasking

Abstract: Media multitasking is an increasingly prominent behavior in affluent societies. However, it still needs to be established if simultaneous use of several modes of media content has an influence on higher cognitive functions, such as divided attention. In this study, attention shifting was the primary focus, since switching between tasks is assumed to be necessary for media multitasking. Two tasks, the number–letter and local–global task, were used as measures of switching ability. The cognitive reflections task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
9
0
4
Order By: Relevance
“…However, studies of the relationship between media multitasking and task-switching performance have yielded mixed results (for a summary, see Uncapher & Wagner, 2018). Some researchers obtained evidence consistent with the pattern described earlier, such that media multitasking scores were negatively correlated with switch costs (Alzahabi & Becker, 2013;Elbe, Sörman, Mellqvist, Brändström, & Ljungberg, 2019). Other researchers found the opposite pattern, with larger switch costs for heavy than for light media multitaskers (Ophir et al, 2009;Wiradhany & Nieuwenstein, 2017, Experiment 1).…”
Section: Introductionmentioning
confidence: 85%
“…However, studies of the relationship between media multitasking and task-switching performance have yielded mixed results (for a summary, see Uncapher & Wagner, 2018). Some researchers obtained evidence consistent with the pattern described earlier, such that media multitasking scores were negatively correlated with switch costs (Alzahabi & Becker, 2013;Elbe, Sörman, Mellqvist, Brändström, & Ljungberg, 2019). Other researchers found the opposite pattern, with larger switch costs for heavy than for light media multitaskers (Ophir et al, 2009;Wiradhany & Nieuwenstein, 2017, Experiment 1).…”
Section: Introductionmentioning
confidence: 85%
“…A recent neuroimaging study further points to altered memory retrieval in high media multitaskers, owing to more frequent attentional lapses during the processing of memory retrieval cues (Madore et al, 2020). Other studies did not always replicate these results Elbe, Sörman, Mellqvist, Brändström, & Ljungberg, 2019;Minear et al, 2013;Seddon, Law, Adams, & Simmons, 2018) or suggested that the relationships between levels of media multitasking and cognitive performance may be non-linear (Cardoso-Leite et al, 2016;Shin, Linke, & Kemps, 2020). The results seem clearer when using surveys and self-reports rather than computerized tests (Magen, 2017): media multitasking has been associated with deficits in self-reported everyday executive and attentional functions (Baumgartner, Weeda, Heijden, & Huizinga, 2014;Magen, 2017;Ralph et al, 2014;Rogobete, Ionescu, & Miclea, 2020) and could be particularly detrimental at younger ages where executive functions develop intensely (Baumgartner, van der Schuur, Lemmens, & te Poel, 2018; see also Srisinghasongkram, Trairatvorakul, Maes, & Chonchaiya, 2020).…”
Section: Media-multitaskingmentioning
confidence: 96%
“…В других исследованиях эти результаты не были воспроизведены [76,77]. Более того, некоторые исследователи сообщают о повышении внимания на фоне высокой степени медиамногозадачности [78,79].…”
Section: связь использования цифровых устройств с отдельными когнитивными функциямиunclassified